Credit booms in the countries of the Eurasian Economic Union. Are they related? - Vymyatnina, Yulia V.; Antonova, Daria (Credit booms w krajach euroazjatyckiej unii gospodarczej. Analiza powiązań, 2014)
In this paper we analyze the dynamics of domestic credits in the three countries of the recently formed Eurasian Economic Union: Russia, Belarus and Kazakhstan to see if it affects the dynamics of major macroeconomic variables, and if any interactions between the countries can be found. We have identified one credit boom in each country in the period from 1995:2 to 2014:1. The timings of credit booms in different countries are not related to each other, but rather to external events like the world economic and financial crisis of 2007–2008 or the initiation of the Customs Union between the three countries in mid-2010. The analysis of changes in the real per capita GDP and its main components (consumption, investments and government expenditures) confirms the results of the previous studies regarding growth process in the three countries.
Ekonometria = Econometrics, 2014, Nr 3 (45), s. 102-121
Keywords: post-Soviet integration; credit cycles; Eurasian Economic Union; Russia; Belarus; Kazakhstan; Euroazjatycka Unia Gospodarcza; dynamika kredytów; Rosja; Białoruś; Kazachstan